Numerical analysis of the fuel spray packages penetration and gas inflow from quasi-dimensional di diesel engine numerical model - Mrzljak, Vedran (Array, 2019)
The paper presents two components of developed quasi-dimensional numerical model: spray package penetration and gas inflow from the zone without combustion into the spray packages. Correction of spray package penetration along the fuel spray radial axis is presented and described numerically. Numerical model simulation is validated in several measured operating points of direct injection diesel engine, after which the simulation results are presented. According to numerical model settings, each fuel spray was divided into packages (control volumes). In the same time interval, the shortest penetration was obtained for spray packages located at the fuel spray edge. Before reaching the break-up time spray package penetration was linear and after reaching the break-up time, package penetration had a curved form. Later injected spray packages quickly reached and surpassed earlier injected spray packages because earlier injected spray packages hit “gas wall” in the engine cylinder and they were “braked” with surrounding gas in comparison to packages injected later. Gas inflow from the zone without combustion into the spray packages is the most intensive for spray packages positioned at the fuel spray edge. The simulation shows that the inflow mass from the zone without combustion increases for spray packages injected later.